인간 대장암 세포주에서 Capsaicin에 의한 세포고사에 관한 연구 - 김규열(Gyu Yeol Kim); 양경민(Kyung Min Yang); 표종옥(Jong Ok Pyo); 성무경(Mu Kyng Sung); 박웅채(Ung Chae Park); 최대화(Dae Hwa Choi); 남창우(Chang Woo Nam); 나양원(Yang Won Nah); 고병균(Byung Kyun Ko); 박건춘(Kun Choon Park); 임영철(Young Cheol Im); 김병삼(Byung Sam Kim); et al. (Annals of surgical treatment and research, 2002)
Purpose: Numerous investigations have been conducted in order to determine the potential carcinogenic or chemopreventive activity of capsaicin. The aim of this study is to characterize the effects of capsaicin on colon cancer cells, and provide valuable information concerning the application of capsaicin in chemoprevention as well as for therapeutic purposes. Methods: CoLo320DM and LoVo cells (human colon cancer cell line) were treated with capsaicin. In order to access cell viability and altered morphology, an MTT assay was performed and the cells were microscopically examined. Decreasing DNA staining was accessed by FACS. The cells were stained with FITC labeled annexin V and analyzed by FACS to detect cellular membrane alteration during apoptosis. The cells were stained with DiOC6(3) and Hydroethidine and analyzed by FACS in order to access ROS and ΔΨm. Results: Capsaicin decreased cell viability in a dose-dependent manner. Capsaicin produced a cell morphology corresponding to the apoptotic features including cell shrinkage and chromatic condensation. Capsaicin treated cells induced a loss of nuclear DNA leading to hypoploidy in a dose-dependent manner. Cells were excluded by double staining with PI and FITC labeled annexin v and detected by FACS. We show that treatment of CoLo320DM, L0Vo cells with increasing concentrations of capsaicin parallel an increase in the percentage of red fluorescent cells (HE→Eth) that reflect ROS hypergeneration and a decrease in the percentage of green fluorescent cells that reflect ΔΨm disruption. Conclusion: These results clearly demonstrate that capsaicin-induced colon cancer cell death is apoptotic. (J Korean Surg Soc 2002;62:103-111) KCI Citation Count: 1